Equilibrium Trade Regimes: Power- vs. Rules-Based - Cecilia Carvalho; Daniel Monte; Emanuel Ornelas (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Members of the World Trade Organization are increasingly disregarding its rules, raising concerns about the future of the multilateral trading system. To analyze the sustainability of the rules-based trade regime, we develop a dynamic framework of stochastic asynchronous games where the leading country determines the trade regime and leadership changes over time. We show that transitioning from a power-based to a rules-based regime requires the presence of a hegemonic power - i.e., a country significantly larger than all others. Non-hegemonic leading countries benefit from a power-based regime, but may nevertheless uphold rules anticipating that they can lose their dominance in the future. We find that the long-term viability of a rules-based equilibrium hinges on the cost of establishing it, which must be neither too small nor too large, on countries' discount factors and on the degree of turnover in world leadership, both of which must be sufficiently large. In a bipolar state, free-riding and market-power forces further undermine the feasibility of rules-based equilibria. We also highlight the trade-offs that a redesign of the WTO rules must face to remain viable. If the leading country becomes shortsighted, the system needs to become more efficient, offer more latitude to the leading country, or even exclude it from the system.
Keywords: F02; F13; F53; 330; hegemonic stability theory; World Trade Organization; trade agreements